Математичне моделювання термомеханічних процесів у пружних тілах із врахуванням локального зміщення маси - Бурак, Я.Й.; Чапля, Є.Я.; Кондрат, В.Ф.; Грицина, О.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
Using the methods of continuum mechanics and non-equilibrium thermodynamics, a model for coupled processes in thermoelastic isotropic solids is proposed taking into account the local displacement of a mass which is caused, for example, by a body structure ordering. It is shown that this approach results in expanding the state parameters space, non-local constitutive equations, redefining the stress tensor, and occurrence of additional volume forces.